1987
DOI: 10.1007/bf02555261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forskolin on bone resorption in the absence and presence of parathyroid hormone and calcitonin

Abstract: Release of previously incorporated 45Ca from fetal rat long bones was determined with the diterpene forskolin, both in the absence and presence of parathyroid hormone (PTH) and calcitonin (CT). In the absence of hormone, increased bone resorption was observed with 10(-7)M forskolin, but biphasic responses, consisting of initial decreases in 45Ca release that were followed by increased calcium mobilization, were produced with 10(-6)M and 10(-5)M forskolin. Inhibition of 45Ca release was pronounced and delayed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The cellular effects of PTH on osteoblast-like cells include stimulation of proliferation (Plas et al, 1985;McDonald et al, 1986), inhibition of proliferation at high concentrations (Partridge et al, 1985), elevation of [Ca], in some but not all osteoblast-like cell lines (Lowik et al, 1985;Boland et al, 1986) and the activation of adenylate cyclase (Chase & Aurbach, 1970). The latter action is insufficient to account for all of the effects of PTH (Lerner et al, 1986a;Conaway et al, 1987;Ransjo & Lerner, 1987) and it has been proposed that osteoblasts possess two different receptors for PTH (Lowik et al, 1985). In support of this proposal, Yamaguchi et al (1987) have demonstrated that PTH can elevate [Ca]l by cyclic AMP-dependent and -independent pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular effects of PTH on osteoblast-like cells include stimulation of proliferation (Plas et al, 1985;McDonald et al, 1986), inhibition of proliferation at high concentrations (Partridge et al, 1985), elevation of [Ca], in some but not all osteoblast-like cell lines (Lowik et al, 1985;Boland et al, 1986) and the activation of adenylate cyclase (Chase & Aurbach, 1970). The latter action is insufficient to account for all of the effects of PTH (Lerner et al, 1986a;Conaway et al, 1987;Ransjo & Lerner, 1987) and it has been proposed that osteoblasts possess two different receptors for PTH (Lowik et al, 1985). In support of this proposal, Yamaguchi et al (1987) have demonstrated that PTH can elevate [Ca]l by cyclic AMP-dependent and -independent pathways.…”
Section: Introductionmentioning
confidence: 99%
“…(11.34.35) Based on the observations that stimulation of the adenylate cyclase-cyclic AMP system by dibutyrylcyclic AMP,(4.5) phosphodiesterase inhibitor^,'^.^^) forsko-1in,(8. [37][38][39] and cholera is substantially delayed compared to the effect of PTH, we have suggested that the rapid activation of osteoclasts is not mediated by cyclic AMP. However, the late bone resorptive response to nonreceptor-mediated cyclic AMP stimulation may very well be related to the capacity of PTH to enhance the formation of new osteoclasts, although this interpretation needs to be confirmed by morphologic data.…”
Section: Discuss'ionmentioning
confidence: 73%